Evaluation of strip rolling directly from the semi-solid state - Lima Filho, Antonio de Padua; Yamasaki, Marcio Iuji (Trans Tech Publications Ltd, 2006)
defect metal alloy strip when thixorolling directly from the semi-solid state. To facilitate the study lead/tin alloys were chosen for their relatively low operating temperature. The objective is to extrapolate these findings to the higher temperature aluminium, alloys. Three alloys (70%Pb30%Sn, 60%Pb-40%Sn, 50%Pb-50%wtSn) were used particularly to study the influence of the solidification interval. The equipment consists of a two roll mill arranged as an upper and lower roller, where both rollers are driven at a controlled speed. The lower roller is fed with semi solid alloy through a ceramic nozzle attached to the lower end of a cooling slope. Several types of nozzle and their position at the roller were tested. This produced different solidifications and consequently different finished strip. The alloys were first cast and then poured onto the cooling slope through a tundish in order to create a continuous laminar flow of slurry and uniformity of metal strip quality. The pouring was tested at different positions along the slope. The cooling slope was coated with colloidal graphite to promote a smooth slurry flow and avoid the problem of adherence and premature solidification. The metallic slurry not only cools along the slope but is also initially super-cooled to a mush by the lower roller whilst at room temperatures, thus enabling thixorolling. It was also found that the nozzle position could be adjusted to enable the upper roller to also contribute to the solidification of the metallic slurry. However the rollers and the cooling slope naturally heat up. Temperature distribution in these zones was analysed by means of three thermocouples positioned along the cooling slope and a fourth in the base of the semi solid pool within the nozzle. The objective being to design an optimum pouring and cooling system. The formed strip was cooled down to room temperature with a shower of water. Microstructures of the thixorolling process were analysed. The differences in solidification conditions resulted in differing qualities of finished strip and corresponding defect types, all of which are a serious quality issue for the rolled product.
Keywords: thixorolling; strip casting; roll casting; solidification range